Transparency and Accountability of Managing School Financial Resources - Gaspar, Millie Rose; Gabriel, Jocelyn P.; B. Manuel, Manuel; Ladrillo, Divina S.; Gabriel, Evangeline R.; G. Gabriel, Arneil (Journal of Public Administration and Governance, 2023)
Transparency and accountability are essentials to the operation of governments regardless of political systems. They are tools to prevent corruption. Transparency and accountability are twin requirements in managing school financial resources. Transparency as a requirement ensures that sound and efficient utilization of resources is maintained while transparency makes opportunity for greater accountability. The study looks into the behavior of school heads on how they manage financial resources of their schools using the parameters of transparency and accountability. The locale of the study is in the province of Nueva in the Philippines. The findings showed that most school heads and finance staff possess graduate-level educational qualification and experienced financial managers. The least accountability parameter of the respondents is in the domain of asset management while it showed the least scores for transparency domain in the area of budgeting. School financial managers encountered challenges which include policy-related procedures, differences in the market prices of supplies and equipment against the programmed budget, and limited opportunities for seminars/trainings regarding school financial management. The late release of budget allocation to schools, lack of adequate skilled manpower essential for effective budget utilization, engagement of school management on different duties, lack of planning and performance of school activities together with stakeholders and interferences of school principals are among the critical challenges that may render ineffective financial resource utilization in secondary schools.